Identifikasi Jenis-Jenis Tumbuhan Sekitar Mata Air Tiga Rasa Sebagai Upaya Konservasi Air Di Gunung Muria Kudus - Malik, Abdul; Kusumarini, Niken (Al-Hayat: Journal of Biology and Applied Biology, 2019)
The Springs of Tiga Rasa Rejenu is one of the springs located at one of the peaks of the seven peaks in the Muria mountains. The Tiga Rasa Springs are located at the peak of Argo Wiloso Rejenu, Kudus Regency. The diversity of vegetation around the Tiga Rasa Springs has an important role in the sustainability of springs source and discharge. This study aims to determine the composition of plants, vegetation forms, the index of importance value of vegetation components, and the abiotic environment impact around the springs. The method used is explorative descriptive analysis by dividing the area into four research stations based on the direction of the eye. At each research station there are three sample plots. Each station is divided into three sampling points with a size of 20m x 20m for trees, 10m x 10m for poles, and 5m x 5m for saplings and 2m x 2m for seedlings. Abiotic environmental parameters measured are air temperature and humidity, light intensity, soil temperature, soil pH, total dissolved solids, and water salinity. The research results around the Tiga Rasa Rejenu spring are that the H' values at the highest level of see dlings is fern Diplazium esculentum, the H' values at the highest level of saplings is the royal palm tree Roystonea regia, and the H' values at the highest level of poles and trees is Pterocarpus indicus. At all stations obtained average H? value is 1.96 then the vegetation around the Tiga Rasa spring classified to medium plant diversity and medium community stability. Abiotic factors effect on the environmental conditions around the Tiga Rasa Rejenu springs.